A esperan??a como pr??xis teol??gico-pedag??gica: um di??logo entre J??rgen Moltmann e Paulo Freire - Assis, Rog??rio de (2019)
This paper presents results of research about the topic: "Hope as a theological and pedagogical praxis: a dialogue between J??rgen Moltmann and Paulo Freire". This research attempts to answer to the following problem: Is there a relationship between Freire and Moltmann???s ideas about hope that can bring contributions to education? The following two hypotheses will guide the completed work: a) there are strong relationships between Freire and Moltmann???s ideas regarding the topic of hope, b) these relationships point to significant contributions to education. The research aimed to point out commonalities and possible differences between the ideas of Paulo Freire and J??rgen Moltmann in relation to the theme of hope and to search for contributions to education from the research. The theme of hope is discussed very little as a subject in educational literature and even less with practicing educators, hence it is one of the reasons this research was completed, as well as the fact that hope is one of the fundamental aspects of the human being, taking into consideration that without hope being instilled, people can become discouraged, or dismayed and hopeless. This path leads to the near paralysis of human action hindering or even preventing the historical quest for a realization of humanity. Hopeless societies condemn themselves to historical immobility which, as will be seen in the two thinkers, is the very negation of the human condition. The theme of hope, or more precisely active hope, is a theme that cannot be lacking in speeches or in educational practices.